Opening remarks - Nagaraja Ch.; Swamy J.N.; Rajendra J.; Khan M.S.; Vishwanath; Reddy D.S.; Manjunath N.; Dillmann R.; Tarn T.J.; Zhao Q.; Ammi M.; Zuberek W.M.; Sandhu P.S.; Patthira; Newman K.; De Silva Liyanage C.; Hassan S.A.A.; Sun K.W.; Rahman Md.M.; Ordoño E.E.; Sharma R.K.; Mishra P.; Chandel B.S.; Singla E.; Petric T.; Zhong Y.; Jiglar J.; Alemzadeh K.; Asokan T.; Tripathi A.; Tripathi M.; Ram S.; Shrma M.K.; Panday P.N.; Kumar D.; Hinchey M.; Stilman B.; Suraj Z.; Pal S.K.; Sasi S.; Rajan D.; Marshall R.G.; Abraham A.; Peter S D.; Paul V.; Gopakumar V.; Dustdar S.; Soto S.V.; Rausch A.; Angelis L.; Nelson A.L.; Botzheim J.; Bernardino H.S.; Zboril F., Jr.; Ane B.K.; Maeda T.; Sakalauskas V.; Hann G.L.K.; Samek J.; Romero Salguero J.R.; Varghese K.; Kriksciuniene D.; Mathew J.; Reif W.; Mauri G.; Cabrerizo Lorite F.J.; Özcan E.; Cho S.-B.; Paily R.P.; Rezankova H.; Tudjarov B.; Hong W.-C.; De Oliveira J.V.; Flores Romero J.J.; Oskouei R.J.; Cicchetti A.; Roy C.; Segura S.; Samuel C.; Mallet F.; Mernik M.; Punnekkat S.; Waseemulla A. (My University, 2025)
[No abstract available]